2018
DOI: 10.1177/1753193418809785
|View full text |Cite
|
Sign up to set email alerts
|

Functional results of wrist arthrodesis versus arthroplasty with proximal fibula following giant cell tumour excision of the distal radius

Abstract: Twenty-one patients underwent excision of a Campanacci grade III giant cell tumour of the distal radius and had reconstruction using a proximal fibula autograft. We compared the functional results of wrist arthrodesis versus arthroplasty. All 21 patients healed in an average of 8 months, and all have remained disease free. The Musculoskeletal Tumor Society 93, the Disabilities of the Arm, Shoulder, and Hand scores and the grip strength of the operated wrist compared with the contralateral wrist were 93%, 7, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
0
17
1
4
Order By: Relevance
“… 21 , 37 Using proximal fibular heads as substitute for resected distal radius is reasonable because of similarity in shapes and availability of autografts. 8 , 40 However, comparable to osteoarticular allografts, using proximal fibular heads to form new articulations may result in instability and carpal translation, often resulting in radiocarpal osteoarthritis. Yet, moderate to good functional results are reported at short- to mid-term follow-up (mean 3 to 6 years).…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 37 Using proximal fibular heads as substitute for resected distal radius is reasonable because of similarity in shapes and availability of autografts. 8 , 40 However, comparable to osteoarticular allografts, using proximal fibular heads to form new articulations may result in instability and carpal translation, often resulting in radiocarpal osteoarthritis. Yet, moderate to good functional results are reported at short- to mid-term follow-up (mean 3 to 6 years).…”
Section: Discussionmentioning
confidence: 99%
“…Bridging grafts include allograft, fibula autograft, and structure iliac crest bone grafts (ICBG) [15][16][17] . Total wrist arthrodesis with massive allograft possesses several advantages, such as being a simple surgical procedure and avoiding donor-site morbidity.…”
Section: Total Wrist Arthrodesismentioning
confidence: 99%
“…The autogenous grafts are more popular. Qu et al treated eight patients with a total wrist arthrodesis with the use of fibula autograft, and they reported that wrist arthrodesis provided better grip strength and functional outcomes than wrist arthroplasty 16 . However, such a reconstruction may bring complications associated with obtaining an autologous fibular graft 20 .…”
Section: Total Wrist Arthrodesismentioning
confidence: 99%
“…4 Dado el grado funcional que presenta esta región, la reconstrucción del radio distal continúa siendo un desafío y aún no existe una técnica definida como estándar de oro, 5 por lo que se han desarrollado múltiples técnicas quirúrgicas tales como artrodesis parcial o total de muñeca y artroplastia de muñeca con ayuda de aloinjertos, impresiones en 3D o colgajos óseos vascularizados y no vascularizados. [6][7][8][9] Dentro de los colgajos vascularizados, el peroné continúa siendo una opción razonable, por lo que se ha llegado a convertir en uno de los más utilizados cuando se trata de reconstrucción a nivel del antebrazo; 8 sin embargo, se han descrito múltiples complicaciones tales como fracturas, parálisis del nervio peroneo común, aflojamiento del material de osteosíntesis, infecciones, inestabilidad articular y no unión. 5 De éstas, la que se presenta con mayor frecuencia es la no unión; 10 sin embargo, no hay estudios enfocados en el análisis de su tratamiento.…”
Section: Wwwmedigraphicorgmx Introducciónunclassified